A case of severe arthralgia with malignant mesothelioma‐associated hypertrophic osteoarthropathy. Issue 11 (5th October 2016) - Yamakawa, Hideaki; Sekine, Akimasa; Kato, Terufumi; Yamanaka, Yumie; Hagiwara, Eri; Umeda, Shigeaki; Ogura, Takashi
Key Clinical Message: Hypertrophic osteoarthropathy (HOA) is a rare syndrome characterized by the abnormal proliferation of dermato‐osseous tissue. We report a rare case of malignant mesothelioma‐associated HOA who suffered from refractory painful osteoarthropathy. HOA can be associated with malignant mesothelioma and that may be resistant to any treatment. Abstract : Hypertrophic osteoarthropathy (HOA) is a rare syndrome characterized by the abnormal proliferation of dermato‐osseous tissue. We report a rare case of malignant mesothelioma‐associated HOA who suffered from refractory painful osteoarthropathy. HOA can be associated with malignant mesothelioma and that may be resistant to any treatment.